BAHAN AJAR STATISTIKA BERBASIS GENERATIVE LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS - Yenni Yenni; Retno Andriyani (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
This study aims to produce teaching materials and statistical exercises based on generative learning methods; find out the effects of teaching materials on students' mathematical understanding skills in statistical subjects. The subjects of this study were 49 students of the mathematics education program. The study uses design research with stages of development research, namely analysis, design, development, implementation, and evaluation. Data collection techniques with questionnaire validity of material experts, media experts, education experts, interview instruments, student evaluations, and tests. Based on the results of the study, teaching materials and statistical exercises based on generative learning are at a good level. The results of the student evaluation questionnaire regarding the effect of teaching materials are at a good level. The results of the mathematical comprehension ability test on statistical subjects are at a very good level. This can be seen from the value of practicality, namely that the final grade of students in the statistics course is in good and very good grades.